Dual-band reconfigurable circularly polarized antenna with novel phase shifter and beamforming network - Majid Allahverdizadeh; Reza Masoumi; Mohammad Bemani (EURASIP Journal on Wireless Communications and Networking)
Abstract This study presents a novel dual-band phase shifter with reconfigurable capabilities, enabling the implementation of an antenna system that supports switchable right-hand and left-hand circular polarizations. The proposed antenna exhibits high performance in terms of gain and polarization purity across two distinct frequency bands: 2.4 GHz and 5.2 GHz. The design methodology consists of two phases. First, four identical dual-band antennas are developed and optimized for efficient spatial arrangement. Then, a feeding network with one input and four output ports is designed to ensure precise signal distribution. A detailed mathematical model using dual-band transmission line theory and ABCD matrix analysis underpins the design. Integrating these components yields a reconfigurable dual-band circularly polarized antenna system. Full-wave simulations conducted in HFSS confirm that the feeding network delivers equal power to the four output ports. The output phases are 0°, 90°, 180°, and 270° in the first state, and 0°, 270°, 180°, and 90° in the second state, with a maximum phase error of 5°. When coupled with the antenna subarray, the system shows an axial ratio below 1.07 dB in the lower band and below 1.05 dB in the higher band. As a result, robust circular polarization is achieved for both right-hand and left-hand states at the target frequencies of 2.4 GHz and 5.2 GHz. Owing to its precision, reconfigurability, and dual-band operation, the proposed design is well-suited for 5G networks, where it can enhance data rates and minimize interference. Moreover, its compact and low-cost structure supports scalable IoT applications such as smart cities, connected vehicles, and advanced communication systems.